International Burden of Chronic Kidney Disease and Secondary Hyperparathyroidism: A Systematic Review of the Literature and Available Data - Elizabeth Hedgeman; Loren Lipworth; Kimberly Lowe; Rajiv Saran; Thy Do; Jon Fryzek (International Journal of Nephrology)
The international burden of secondary hyperparathyroidism (SHPT) is unknown, but it may be estimable through the available chronic kidney disease and SHPT literature. Structured reviews of biomedical literature and online data systems were performed for selected countries to ascertain recent estimates of the incidence, prevalence, and survival of individuals with CKD and SHPT. International societies of nephrology were contacted to seek additional information regarding available data. Estimates were abstracted from 35 sources reporting estimates of CKD in 25 countries. Population prevalence estimates of CKD stages 3–5 in adults ranged from approximately 1 to 9% (China, Mexico, resp.). Estimates of the population prevalence of maintenance dialysis therapy ranged from 79 per million population (pmp; China) to 2385 pmp (Japan); incidence rates ranged from 91 pmp (United Kingdom) to 349 pmp (United States). Prevalence of SHPT among stage 5D populations was highly variable and dependent upon the disease definition used. Among the few nations reporting, approximately 30–50% of stage 5D patients had serum parathyroid hormone levels >300 pg/mL. Reported incidence and prevalence estimates across the individual nations were variable, likely reflecting differing population demographics, risk factors, etiologies, and availability of treatment through all stages of CKD.